Adipose tissue dysfunction disrupts metabolic homeostasis: mechanisms linking fat dysregulation to disease - Dana Bou Matar; Mahmoud Zhra; Walid Khaled Nassar; Haifa Altemyatt; Asfiya Naureen; Nada Abotouk; Muhammad Affan Elahi; Ahmad Aljada (Frontiers in Endocrinology)
BackgroundMetabolic disease incidence continues rising globally. Adipose tissue dysfunction serves as a crucial pathophysiological mediator. We evaluate molecular mechanisms linking adipose dysfunction to metabolic dysregulation.MethodsWe systematically reviewed literature on adipose biology, stress mechanisms, inflammation, and metabolic networks. Analysis prioritized methodologically robust studies from the past decade.ResultsAdipose dysfunction disrupts metabolic homeostasis through complex molecular networks. Stressed adipocytes exhibit mitochondrial impairment and endoplasmic reticulum (ER) stress. These changes alter inflammatory mediators and adipokine secretion. Brown and beige adipose regulate energy balance via uncoupling protein 1 (UCP1)-mediated thermogenesis. Key transcriptional regulators, PGC-1α and PR domain containing 16 (PRDM16), control thermogenic adipocyte development. Cellular senescence contributes significantly to age-related adipose dysfunction through inflammatory secretory phenotypes. Brown fat also secretes specialized factors influencing whole-body metabolism, emphasizing adipose tissue’s endocrine function.ConclusionAdipose dysfunction represents a critical nexus in metabolic disease pathogenesis. Cellular stress, inflammation, and metabolic dysregulation converge at this point. Novel therapies targeting thermogenic activation and cellular senescence show promise. Despite advancing mechanistic understanding, developing effective interventions remains challenging due to adipose tissue’s complex roles in systemic metabolic regulation.